'Acute micro-coronary syndrome': detailed coronary physiology in a patient with Takotsubo cardiomyopathy. Issue 8 (28th August 2019) - Morrow, Andrew J; Nordin, Sabrina; O'Boyle, Patrick; Berry, Colin
Abstract : Takotsubo cardiomyopathy (TC), otherwise known as stress cardiomyopathy, is characterised by acute, transient left ventricular systolic dysfunction with apical ballooning in the absence of obstructive epicardial coronary stenosis. The presentation of TC mimics that of acute myocardial infarction. More recently there has been a shift towards thinking of TC as a 'microvascular acute coronary syndrome'. Our case is of an 82-year-old woman who presented with TC mimicking acute anterior ST elevation myocardial infarction in the context of sepsis. Slow flow noted in the left anterior descending artery prompted us to perform coronary physiology. Her fractional flow reserve was 0.91, with an index of myocardial resistance of 117 and a coronary flow reserve of 1.6. In combination these results are indicative of microvascular coronary dysfunction in the absence of significant epicardial stenosis.